BARRIERS AND BENEFITS OF TECHNOLOGY INTEGRATION IN EDUCATION: PERSPECTIVES FROM HIGHER SECONDARY STUDENTS - Gnana Jothi J; D. Ponrani (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study explores the barriers and benefits of technology integration in education from the perspectives of higher secondary students in Kanyakumari District. It highlights how technology has transformed learning environments, enabling access to a vast array of resources and interactive learning tools. The research identifies key benefits, such as enhanced engagement, personalized learning experiences, and improved digital literacy, which are essential in the modern educational landscape. However, it also uncovers significant barriers, including inadequate infrastructure, lack of teacher training, and resistance to change among both educators and students. These obstacles hinder the effective implementation of technology in classrooms. By utilizing qualitative methods, including surveys and interviews, this study aims to provide insights that can inform policy recommendations and strategies for enhancing technology integration in local educational institutions, ultimately fostering a more conducive learning environment for students in Kanyakumari District. Both primary data and secondary data has been collected. Simple random sampling method was used to gather 200 respondents has been used from Kanyakumari District in order to obtain the relevant data.